Relationship mapping between stress and academic performance in higher education (Research, Society and Development, 2020)
This paper aims to map the relationship between stress and academic performance of students in higher education. The exploratory investigation of qualitative nature was based on discussions about the impact of stress on the performance of cognitive functions. The research context was the higher course in Technology in Environmental Management at the Federal Institute of Education, Science and Technology of Rio Grande do Norte, campus Mossoró. Semi-structured interviews were used to build data. Students from the 1st and the 5th semester of the course were interviewed to identify their perceptions about academic stress. A questionnaire was used to construct the data. Students from the 1st to the 5th semester of the course participated in the research to identify their perceptions about academic stress. Simultaneously, these perceptions were related to their performance. Data analysis revealed that stress is more related to pressure for satisfactory grades and is more evident among students in the 5th semester. It is concluded that stress is perceived throughout academic life and influences academic performance in more advanced semesters. Suggestions of attitudes or activities that can minimize the stress perceived by the students are recommended.